Primerjava rezultatov cementacije zaščitnih verig v soli in plinu - Legat, Franc (Kovine zlitine tehnologije, 1997)
In the paper the shape of the links of protective chains for heavy machine wheels, hardness on surface and over the link section after case hardening in gas and salt as well as the results of field testing of chains are presented.
Keywords: verige; stroji; kaljenje; cementacija; trdota